Impact of Sintered Temperature on the Heat and Cation Transport in NaK-BASE Tube - Guan, Ning; Chen, Weijian; Gao, Yan (Frontiers in Energy Research, 2021)
Alkali metal thermoelectric converter (AMTEC) is a clean energy converter that can be coupled with biomass for power generation. In present research, the transport of heat and cation was investigated in NaK-BASE tubes prepared at different sintered temperatures. The heat conduction and the fractal model were employed to investigate the temperature distributions based on the microstructures of the NaK-BASE tubes sintered at different temperatures, and the transport of Na+ and K+ in NaK-BASE tube was simulated by Poisson-Nernst-Planck multi-ions transport model, and the cation concentrations and surface charge densities were obtained in the NaK-BASE tubes with different temperatures. The results showed that microstructure of the NaK-BASE was related to the sintered temperature, and the microstructure of the NaK-BASE impacted the temperature distribution, the cation concentration and the surface charge density of Na+ and K+ in the NaK-BASE tubes. At the same heat source temperature, the average temperature in the NaK-BASE prepared at high sintered temperature was higher than that prepared at low sintered temperature. In addition, the increase of the average temperature resulted in the increase of the cation concentration and the surface charge density of Na+ and K+ in the NaK-BASE, therefore, the performance of the NaK-AMTEC could be enhanced by increasing the sintered temperature and the average temperature of the NaK-BASE.